Analisis Produksi Sektor Industri Manufaktur Di Indonesia - Meirani; Sri Ulfa Sentosa (Universitas Negeri Padang, 2026)
Abstrack This study aims to analyze the effects of labor, raw materials, and electricity consumption on manufacturing sector output in Indonesia. The data used consists of panel data for 34 provinces in Indonesia from 2017 to 2023, obtained from publications of the Indonesian Central Statistic Agency. This study employed panel data regression analysis, with the Random Effect Model selected as the preferred model. The findings indicate that the variabels of labor, raw materials, and electricity consumption have a positive and significant impact on manufacturing sector production in Indonesia. Consequently, the government’s role is essential in improving human resource quality, developing strategies for optimalraw material processing, and adopting energy-efficient technologies to ensure continuity in the production process. The Return to Scale value is 1, indicating a Constant Return to Scale condition.